Proteomic analysis reveals a potential role for extracellular vesicles within the erythroblastic island niche - Ventura, Telma; Fidanza, Antonella; Wilson, Marieangela C.; Ferguson, Daniel C. J.; Lewis, Phillip A.; May, Alisha; Taylor, Helen; Rimmer, Michael P.; Gregory, Christopher D.; Frayne, Jan; Forrester, Lesley M. (Frontiers in Molecular Biosciences, 2024)
Erythroblastic island (EBI) macrophages play an essential role in the production and maturation of the vast numbers of red blood cells (RBCs) that are produced throughout life.Their location within the bone marrow makes it difficult to study the cellular and molecular interactions associated with their action so we have used an in vitro model of the EBI niche using macrophages derived from human induced pluripotent stem cells (hiPSCs). We previously demonstrated that the activation of the transcription factor KLF1 enhanced the activity of hiPSC-derived EBI macrophages. To elucidate the mechanisms associated with EBI-like activity we carried out a quantitative proteomic analysis. Gene ontology analysis showed that many of the proteins upregulated by KLF1 were protein-binding factors, some of which were associated with the cell membrane or extracellular vesicles. We demonstrated that filtration of macrophage-conditioned media resulted in a reduction in the supportive effects on erythroid cell viability and maturation implying a role for extracellular vesicles but this was not KLF1 dependent. Pathway analyses of the proteomic data revealed that proteins upregulated by KLF1 were associated with the citric acid cycle, pyruvate metabolism and ATP synthesis indicating that KLF1-activated macrophages had a metabolic profile comparable to a pro-reparative phenotype. This study has generated a proteomic dataset that could provide new insights into the role of macrophages within the EBI niche and has indicated a potential role for extracellular vesicles in the differentiation and maturation of RBCs in vitro. Further research will aid in the production of RBCs in vitro for use in disease modelling and cell therapy.